The Role of Web Technologies in Promoting Learner Autonomy among EFL University Students - Oubadi, Youssef; Lamkhanter, Fouzia (International Journal of Language and Literary Studies, 2024)
Technological advancements have brought about several environmental, economic and social challenges for the entire world. Nevertheless, no one can deny that these forces have offered infinite opportunities for progress and development for humanity. The digital revolution has dramatically affected many domains such as work and education. Perhaps one of the main aspects of this revolution in education is online learning which allows students to easily access resources and self-direct their learning. The current paper attempts to examine the role of using Web technologies in fostering learners’ autonomy. It also aims to explore students’ experiences with online learning and how they perceive its relevance to the enhancement of autonomous abilities. To attain these objectives, a mixed-method approach is adopted to collect data utilizing questionnaires and semi-structured interviews. The participants are Moroccan university students in the English departments, and data is analyzed using descriptive statistics and thematic analysis. The results show that the participants display high levels of autonomous behaviours as students value their experiences with online learning. The findings also indicate that most students are willing to be more responsible for their own learning when using online platforms that offer, flexibility, interaction, and interesting autonomous practices of language learning.